An empirical study on the relations between EEG alpha-beta entropy & EQ- IQ test scores - Vakili, S.; Tehranchian, N.; Tajziehchi, M.; Rezazadeh, Iman Mohammad; Xiangyu Wang (Proceedings of 2012 IEEE-EMBS International Conference on Biomedical and Health Informatics, 2012)
In this paper, the relationship between the subjects' brain waves and the relative Emotional Quotient (EQ) and Intelligence Quotient (IQ) has been investigated. In this study, the intensity of correlation between the entropy of Alpha and Beta brain waves and the IQ and EQ has been evaluated over thirty healthy subjects (15 males, 15 females, and aged 21-25 year old) who participated in the experiments by calculating Pearson correlation coefficients. Each subject was asked to fill out a sixty-question questionnaire that was developed based on the Adult Raven IQ test in a 20-minute time slot. Simultaneously, the subject's EEG signals were recorded to extract Alpha and Beta sub-bands and their entropies over each 128msec time slots. It was found that the participants who have high EQ (over 110), had their entropy of Beta band increased significantly. In contrast, the subjects with the entropy of Alpha band in high IQ (over 120), decreased significantly.